الفتوحات الاسلامية لبلاد فارس وبلاد ما وراء النهر في ضوء الدراسات الاستشراقية(17-101هـ/638-719م) (Journal of the College of Basic Education, 2026)
The study of the Islamic conquests of Persia and Transoxiana according to an Orientalist perspective was a collection of historical information scattered throughout the folds of Orientalist books and articles. It was not complete, but rather scattered, as it was collected and presented in a complete manner in order to link the events and to show the extent of the importance of the Islamic conquests of Persia and Transoxiana. Beyond the river, spreading Islam, imposing the jizya on the inhabitants of the cities conquered by force or by peace, introducing reconstructions such as building a mosque and the accompanying establishment of baths for ablution and cleanliness, creating an emirate house, and clarifying the slander of the Orientalists and their bias towards these Islamic conquests, as the Orientalists mentioned several reasons, including religious and economic ones The weakness of the Sassanian Empire and the migration of people in search of regions rich in resources, and the Orientalists also addressed the results of the Islamic conquest in order to control the lands and end the Persian imperial authority, but they did not address the lofty goal of these Islamic conquests, which was to spread Islam and peace among the people and liberate them from injustice and tyranny.